Recovery High School: Feasibility of Co-Produced, Peer-Based Mental Health Support for Adolescents - Lin, Theresa; Bari, Samiha; Arbour, Simone (Journal of Recovery in Mental Health, 2026)
Background: Adolescents accessing mental health services face barriers, from long waitlists to lack of age-appropriate programming. Low-barrier early mental health intervention is needed, and the Recovery College model could be an effective approach.Objective: We explored the feasibility of a Recovery College model in the adolescent population, termed Recovery High School, and ascertained the mental health and support needs of this population to inform its development.Method: Information was obtained via semi-structured interviews with mental health clinicians and analysis of data from a mental health hospital’s adolescent waitlist. Themes and trends among adolescents seeking mental health care were developed.Results: Interviews with adolescent clinicians (N=5) yielded nine themes and considerations for Recovery High School. Mental health concerns such as trauma, social issues and emotional dysregulation were identified, and related course topics were suggested. Challenges and logistical considerations such as scheduling and age of students in courses were identified. Caregiver needs included connection and system navigation. Data from the outpatient waitlist revealed mood and anxiety disorders to be the most prevalent issue facing adolescents.Conclusion: Peer-based co-produced educational courses - Recovery High School, was well supported by adolescent clinicians. With some modifications to the adult model, Recovery College could be developed for adolescents and their caregivers.